A novel biallelic variant c.2219T > A p.(Leu740*) in ADGRG6 as a cause of lethal congenital contracture syndrome 9. Issue 1 (9th October 2022) - Shravya, Mangalore S.; Mathew, Mary; Vasudeva, Akhila; Girisha, Katta M.; Nayak, Shalini S.
Abstract :